Representasi Pesan Moral Transformasi Diri dalam Film A Man Called Otto - Ahimsa Damar Galih; Oji Kurniadi (Bandung Conference Series: Public Relations, 2024)
Abstract. Film is a form of mass media that has an important role in the field of communication, film can be seen as a form of mass communication that contains messages and semiotic signs conveyed by filmmakers to the audiences. As a form of mass media, film can represent various types of messages and ideologies that filmmakers want to convey. One of the messages in the film is a moral message. Moral messages are lessons that can be obtained from an event or someone's experience. The film that depicts a moral message is A Man Called Otto, which was released on January 13, 2023 and was directed by Marc Forster. A Man Called Otto is a film that tells the story of Otto's life journey, who struggles with the feeling of loneliness within himself and tries to end his life. However, a new neighbor arrives who can make his life more meaningful and self-transformation The purpose of this study is to find out the meaning of denotation, connotation and myth in the film A Man Called Otto. The method used in this study is a qualitative method with Roland Barthes semiotic analysis. The data collection method is by observing, documenting and studying the literature. And the data analysis technique is the semiotic analysis method of Roland Barthes. The subject of this research is the film A Man Called Otto. Abstrak. Film adalah salah satu bentuk media massa yang memiliki peran penting dalam bidang komunikasi, film dapat dipandang sebagai bentuk komunikasi massa yang mengandung pesan-pesan dan tanda semiotika yang disampaikan oleh pembuat film kepada penonton. Sebagai bentuk media massa, film dapat merepresentasikan berbagai macam jenis pesan dan ideologi yang ingin disampaikan oleh pembuat film. Salah satu pesan dalam film adalah pesan moral. Pesan moral merupakan pelajaran yang dapat diperoleh dari sesuatu peristiwa, pengalaman seseorang. Film yang menggambarkan sebuah pesan moral ialah A Man Called Otto yang dirilis pada 13 Januari 2023 dan disutradai oleh Marc Forster. A Man Called Otto merupakan film yang menceritakan perjalanan hidup Otto yang berjuang melawan rasa kesepian dalam dirinya hingga berupaya untuk mengakhiri hidup. Namun, datanglah seorang tetangga baru yang bisa membuat hidupnya bisa lebih berarti dan bertransformasi diri. Tujuan dalam penelitian ini untuk mengetahui makna denotasi,konotasi dan mitos pada film A Man Called Otto. Metode yang digunakan dalam penelitian ini adalah metode kualitatif dengan analisis semiotika Roland Barthes. Metode pengumpulan dengan melakukan observasi, dokumentasi dan studi pustaka. Dan teknik analisis data yaitu dengan metode analisis semiotika Roland Barthes. Subjek penelitian ini adalah film A Man Called Otto.